If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -910 = -26a Solving -910 = -26a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '26a' to each side of the equation. -910 + 26a = -26a + 26a Combine like terms: -26a + 26a = 0 -910 + 26a = 0 Add '910' to each side of the equation. -910 + 910 + 26a = 0 + 910 Combine like terms: -910 + 910 = 0 0 + 26a = 0 + 910 26a = 0 + 910 Combine like terms: 0 + 910 = 910 26a = 910 Divide each side by '26'. a = 35 Simplifying a = 35
| 4(n-3)-2(n+2)=3(n+5)-n | | a+x=t | | x^2-4k+1=-5 | | 60=6(6-2x) | | 5x+7=3x+3 | | 11x+5=15+10x | | 3x^4=360 | | f+3=15 | | 4x+3(x-1)=-2(x-3)+9 | | 2/5(x-4)=2x | | f-3=15 | | 2f+3=15 | | 2g=60+5g | | 7x=4x+18 | | 4*.25x-2=0 | | 2f-3=15 | | -2x+1+9x-5=7x-4 | | p+9=4p-12 | | (-(x-4)(x-4))=0 | | 8x-6+x-1=13 | | 3y=7+15 | | 8(k-3)=32 | | 4j-3j= | | (n+4)*9=72 | | 4s-13=15 | | (n-7)*3=12 | | 42x+3=43x | | (n+2)*5=20 | | 7x-1=3(x+2) | | 4a-1a=4 | | 4a-1a=4# | | 4-3(x+1)=10 |